"Kampong Takwā" thāng rō̜t khō̜ng kānkǣ panhā čhangwat chāidǣn Tai - Suwat Khongpǣn (Chumchon Satthā, 2009)
Use of Islamic faith as way for community development in the Thai Southern border provinces.